From waste to growth: Mushroom residues in horticulture - Bogevska, Z; Todorova, K; Markoski, M; Popsimonova, G; Agic, R; Davitkovska, M (Biotechnical Faculty of the University of Montenegro, 2025)
The rapid global expansion of mushroom cultivation has established it as an important agribusiness sector and a promising strategy for sustainable management of agricultural residues. Nevertheless, this growth has resulted in the annual accumulation of millions of tons of spent mushroom substrate (SMS), creating significant environmental and logistical challenges. On average, approximately five kilograms of SMS are generated for every kilogram of fresh mushrooms harvested. In North Macedonia, the mushroom industry similarly produces considerable quantities of SMS, which presents an opportunity for its reutilization as a growing substrate for horticultural crops. In this context, the present study investigated the physical and chemical properties of SMS derived from the fast-growing oyster mushroom (Pleurotus ostreatus). The results demonstrated that the substrate exhibits favorable physical characteristics, including low bulk density, homogeneous texture, and low electrical conductivity, making it suitable for incorporation into horticultural substrate mixes. Chemically, the substrate was found to be low in nitrogen and phosphorus but contained moderate to sufficient levels of potassium, while its exceptionally high organic matter content enhances its potential as a soil conditioner. Literature review indicates that mushroom residues are primarily employed as components of growing media in vegetable and ornamental crop production. Additionally, SMS can serve as a fertilizer, soil amendment, or mulch, providing multifunctional benefits in sustainable horticultural practices. Overall, oyster mushroom SMS represents a valuable resource for horticulture, combining desirable physical properties with nutrient supplementation potential and contributing to circular waste management strategies in the mushroom industry.
Keywords: spent mushroom substrate, growing medium, composition, Pleurotus ostreatus, horticulture